C/EBPβ regulates lipid metabolism and Pparg isoform 2 expression in alveolar macrophages - Dörr, Dorothea; Obermayer, Benedikt; Weiner, January Mikolaj; Zimmermann, Karin; Anania, Chiara; Wagner, Lisa Katharina; Lyras, Ekaterini Maria; Sapozhnikova, Valeriia; Lara-Astiaso, David; Prósper, Felipe; Lang, Roland; Lupiáñez, Darío G.; et al. (Science immunology, 2022)
Pulmonary alveolar proteinosis (PAP) is a syndrome characterized by accumulation of surfactant lipoproteins within the lung alveoli. Alveolar macrophages (AMs) are crucial for surfactant clearance, and their differentiation depends on colony-stimulating factor 2 (CSF2), which regulates the establishment of an AM-characteristic gene regulatory network. Here, we report that the transcription factor CCAAT/enhancer binding protein β (C/EBPβ) is essential for the development of the AM identity, as demonstrated by transcriptome and chromatin accessibility analysis. Furthermore, C/EBPβ-deficient AMs showed severe defects in proliferation, phagocytosis, and lipid metabolism, collectively resulting in a PAP-like syndrome. Mechanistically, the long C/EBPβ protein variants LAP* and LAP together with CSF2 signaling induced the expression of Pparg isoform 2 but not Pparg isoform 1, a molecular regulatory mechanism that was also observed in other CSF2-primed macrophages. These results uncover C/EBPβ as a key regulator of AM cell fate and shed light on the molecular networks controlling lipid metabolism in macrophages.
CRIS-Team Scopus Importer:2022-09-30